Transnational penal cultures
1 online resource (xv, 234 pages)
Keywords: "Focusing on three key stages of the criminal justice process - discipline, punishment, and desistance - and incorporating case studies from Asia, the Americas, Europe, Africa, and Australia, the thirteen essays in this collection are based on exciting new research that explores the evolution and adaptation of criminal justice and penal systems, largely from the early-nineteenth century to the present. They range across the disciplinary boundaries of History, Criminology, Law and Penology. Journeying into and unlocking different national and international penal archives, and drawing on diverse analytical approaches, the essays forge new connections between historical and contemporary issues in crime, prisons, policing, and penal cultures, and challenge traditional western democratic historiographies of crime and punishment and categorisations of offenders, police and ex-offenders. The individual essays provide new perspectives on race, gender, class, urban space, surveillance, policing, prisonisation and defiance and will be essential reading for academics and students engaged in the study of criminal justice, law, police, transportation, slavery, offenders and desistance from crime"-- "The histories of prisons, transportation, and police are well-established fields of enquiry. In recent years scholars have begun to recognise the subjects' global dimensions and the potential for comparative studies to provide new critical insights. This book offers original and critical essays from leading scholars working on crime, police, and prisons across the continents of Asia, the Americas, Europe, Africa, and Australia. Drawing on a range of disciplinary tools and critical analyses, and utilising a comparative transnational lens, Transnational Penal Cultures explores interdisciplinary connections between, and challenges to traditional western democratic historiographies, as well as categorisations of offenders, police and ex-offenders. "--